Assessment and analysis of outpatient medication errors related to pediatric prescriptions - Amira B. Kassem; Haitham Saeed; Noha A. El Bassiouny; Marwa Kamal (Elsevier, 2021)
Background: Medication errors are the errors that impact the efficacy and safety of the therapy. The impact of medication errors is higher for certain subjects, such as pediatrics, who require more attention. Hence, the current study aimed to investigate the types and frequency of outpatient medication errors of pediatric subjects related to different prescription types. Methods: A cross-sectional study was carried in several community pharmacies to record the medication errors found in outpatient pediatric prescriptions by gathering data from the outpatient prescriptions besides direct counseling with the subjects and their parents. Many medical resources (disease and drug-related) were used for checking the different aspects of medication errors. The data collection process included a preprepared sheet containing several items representing the medication errors in addition to a counseling session. Data were expressed as percentages and compared through the Chi-square test for results of handwritten and computerized prescriptions. Results: 752 outpatient pediatric prescriptions were recruited in the study as they involve medication errors. Among the highest percentage of medication errors was the absence of essential data in the prescription, such as diagnosis, age, and weight. The duration of the therapy and contraindication for some of the prescribed medications were among the highest recorded errors. Among the critical errors were the drug interaction and drug duplication that directly affect the drug's efficacy and safety. There was a significant difference between computerized and handwritten prescriptions regarding the number of medication errors related to each type. Conclusion: Medication errors related to outpatient pediatric prescriptions vary from one to another prescription with predominant errors that influence the therapy's safety or efficacy. The role of patient counseling and prescription checking is critical for improving patient therapy.